Performance Evaluation of Asphalt Mixtures with Rediset LQ-1200 Additive - Nguyen, Thanh Len; Le, Van Phuc; Nguyen, Quang Phuc; Dang, Gia Bao; Nguyen, Minh Hong Nhan (Engineering, Technology & Applied Science Research, 2024)
One of the primary causes of premature pavement deterioration in Asphalt Concrete (AC) mixtures is the breaking of the adhesive bond between the aggregate and the binder. The purpose of this study is to assess the performance characteristics of AC mixture utilizing the Rediset LQ-1200 additive. In order to achieve this goal, tests such as the Marshall Stability (MS), Marshall Stability Ratio (MSR), Indirect Tensile (IDT), indirect tensile cracking, and Wheel Tracking (WT) were deployed to evaluate the mechanical properties of AC mixtures. The findings demonstrated a considerable improvement in the physical parameters of the AC mixture with the Rediset LQ-1200 additive compared to the base AC mixture. The MS and MSR were improved by about 28% and 13%, respectively, while the AC mixture’s resistance to rutting and cracking was efficiently increased.